Estatismo y movimiento, orden cósmico y desequilibrio en el Libro 4 de La Eneida (Minerva, 2019)
The eim of this paper is the semantic analysis of the images of stillness and movement in Aeneid 4. The contribution of these images in the configuration of the characteres of Dido and Aeneas will be considered, and, through it, the shape of a basic subject in the virgilian aesthetics: the concept of cosmic order and the presence of agents of imbalance in it.